PERSONAL BRANDING TERHADAP MINAT SISWA DALAM MEMILIH SEKOLAH BERBASIS PESANTREN - Nailatul Muna; Sekar Meika Chandra (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2022)
Syubbanul Wathon Vocational School is a school under the auspices of the Syubbanul Wathon Foundation; one of the owners is K.H Yusuf Chudlori, a young millennial cleric who actively spreads symbols through social media with 103 thousand followers. This study aims to determine the influence of K.H Yusuf Chudlori personal branding on student interest in school at Syubbanul Wathon Vocational School. The research method used is quantitative; the sample used is 280, which are taken randomly. The data analysis technique used is simple linear regression analysis. Based on the results of the data analysis, it was found that the t-count was 6.445 with a sig of 0.000 (p <0.05), so the decision was to reject Ho and accept Ha. It can be concluded that the personal branding variable is proven to have a significant effect of 13% on student interest in school at Syubbanul Wathon Tegalrejo Vocational School, Magelang.